MENINGKATKAN MINAT BELAJAR SISWA SEKOLAH DASAR PADA MATA PELAJARAN PENDIDIKAN JASMANI - purwanti, yayuk; Putri, Fitri Ika Amelia; Sulhaliza, Ammylia Prihatini; Fakhriyah, Fina; Ismaya, Erik Aditia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
Physical education is an educational process with the help of motor activity, which aims to improve physical fitness, motor skills, emotional intelligence, education and the formation of a healthy and active lifestyle. The purpose of this research is to study the literature on sports interest among elementary school students. The research method used in this study is the SLR (Systematic Literature Search) method. Data collection was carried out by converting all documents containing similar research into research reports. This study uses articles from seven national journals taken from the Google Scholar database using the Publish or Perish program. Surveys show that elementary school students still have little interest in physical education. The purpose of this research is for teachers to be more creative in conveying content and convincing students, and for teachers to motivate students to attend physical education classes.